2016
DOI: 10.1002/adma.201505559
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and Stretchable Optoelectronic Devices using Silver Nanowires and Graphene

Abstract: Many studies have accompanied the emergence of a great interest in flexible or/and stretchable devices for new applications in wearable and futuristic technology, including human-interface devices, robotic skin, and biometric devices, and in optoelectronic devices. Especially, new nanodimensional materials enable flexibility or stretchability to be brought based on their dimensionality. Here, the emerging field of flexible devices is briefly introduced using silver nanowires and graphene, which are famous nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(92 citation statements)
references
References 37 publications
(33 reference statements)
0
87
0
Order By: Relevance
“…[91] Challenges common to all NW network approaches are their poor chemical stability and tendency to oxidize, their large surface roughness, their weak adhesion to the substrate and high contact resistance to adjacent functional layers in devices. To overcome some of these challenges, NWs can be embedded in transparent dielectrics, conductive polymers, [92] graphene oxide, [93] and metal oxides. [94] Stability data on NW electrodes are not widely reported, but recent efforts indicate possibilities to improve the performance of transparent NW electrodes.…”
Section: Metal Nanowires Nano-and Microgrids and Ultrathin Filmsmentioning
confidence: 99%
“…[91] Challenges common to all NW network approaches are their poor chemical stability and tendency to oxidize, their large surface roughness, their weak adhesion to the substrate and high contact resistance to adjacent functional layers in devices. To overcome some of these challenges, NWs can be embedded in transparent dielectrics, conductive polymers, [92] graphene oxide, [93] and metal oxides. [94] Stability data on NW electrodes are not widely reported, but recent efforts indicate possibilities to improve the performance of transparent NW electrodes.…”
Section: Metal Nanowires Nano-and Microgrids and Ultrathin Filmsmentioning
confidence: 99%
“…Graphene is a highly recommended material for TCFs due to its excellent electrical conductivity and optical transmittance in the visible and near‐infrared (NIR) region . Moreover, graphene exhibits high flexibility and outstanding chemical stability .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they can be formed on various flexible substrates by a transfer process under non-vacuum and low temperature conditions. [29][30][31][32][33] Besides their use as transparent electrodes, carbon-based thin films, especially the CNT thin film, are good candidates for the semiconducting channel of TFTs, and many impressive research achievements have been reported to demonstrate wide range of possible uses for carbon-based flexible electronics. [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] It is recognized that carbon is a unique element that can be used in both the electrode and the channel for the fabrication of all-carbon TFTs and ICs for extremely flexible and transparent electronics.…”
Section: Introductionmentioning
confidence: 99%